If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) = 4(1 + x) + 5 Reorder the terms: 3(-1 + x) = 4(1 + x) + 5 (-1 * 3 + x * 3) = 4(1 + x) + 5 (-3 + 3x) = 4(1 + x) + 5 -3 + 3x = (1 * 4 + x * 4) + 5 -3 + 3x = (4 + 4x) + 5 Reorder the terms: -3 + 3x = 4 + 5 + 4x Combine like terms: 4 + 5 = 9 -3 + 3x = 9 + 4x Solving -3 + 3x = 9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 3x + -4x = 9 + 4x + -4x Combine like terms: 3x + -4x = -1x -3 + -1x = 9 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + -1x = 9 + 0 -3 + -1x = 9 Add '3' to each side of the equation. -3 + 3 + -1x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 9 + 3 -1x = 9 + 3 Combine like terms: 9 + 3 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| A/9-7=-1 | | 505.80=170+1.15X | | 1/8t=-9 | | 52/200 | | 3k+8k-9k-2k+3k+12= | | 31=c/31 | | 0.2(10-5)=5c-16 | | 1.5x+(3x-6)=10 | | n-7/51=11/17 | | 8-x+1=2x-12 | | 1x+1y=99 | | 7x+x-210=150 | | 12-2x=8+4x | | x+110+75=180 | | -3x+4=5x-3 | | 4x-16y=-44 | | 28-7x=3x-12 | | -8x+28=-4x+56 | | 6y-3=2y-15 | | (4x-1)/(3x)4x | | 23x-4=180 | | 8/7=3/3b | | 23x-4+4x-1+9x-31=180 | | 8r=45 | | .5(x-10)=7 | | 19x-6+4x=180 | | x^2+y^2-10y+25=36 | | x=yx | | 5y+3=42 | | f-32/1.8 | | 12x-1/2x^=0 | | 7n+5=58 |